(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
E-learning software systems have been proposed by many researchers and academics as alternative platform for pedagogy other than traditional face-to-face. One of such information systems (IS) is Virtual learning Systems (VLS). VLS are becoming an increasingly common form of education due to the need for a platform that provides ability to connect people with required sets of skills, regardless of their location in the world.Â However, user satisfaction has always been a major factor in the success of software, regardless of whether the software is closed proprietary or open source software (OSS). Although user-centred designs are gaining recognition among virtual learning systems (VLS) community, many design scenarios still do not incorporate usability as one of their primary goals. Accordingly, many individuals believe that if VLS was more usable, its popularity would increase tremendously. Although there are strong usability models for IS, there is still potential to improve the usability of VLS.Â The usability assessment of VLS projects is an area where relatively little research has been conducted, and, accordingly, the main contribution of this work is a methodology that evaluates the usability maturity of a VLS project. Consequently, the study presents a usability maturity model that is aimed at usability-related issues for virtual learning system projects. The model to be developed is a response to a need for measuring the extent to which virtual learning systems software projects support usability. Specifically, it is intended for assessing and improving the usability aspect in VLS software development. The deductions from the research findings will be especially useful to e-learning practitioners, ICT and Education professionals and policy makers and researchers in Virtual Learning Environments.